Development of Digital-Based Teaching Material Management for Teachers of SMP Negeri 13 Ternate City - Andy Andy; Ramli Yusuf; Mubin Noho; Minggusta Juliadarma; Asrul Usman; Faidah T. Hi. Jafar (Archipelago, 2021)
There are several factors that determine the success of the learning process, one of which is teaching materials. Teaching materials need to be designed in such a way that they can support the achievement of expected learning outcomes. On the other hand, in the current era of the COVID-19 pandemic, the government and all stakeholders must work together and think hard about dealing with this virus. One of the efforts that can be done to improve the ability of these teachers is to conduct training for teachers of SMP Negeri 13 which aims to improve the quality of teaching and learning in schools. The community service activities in this report aim to improve the ability of junior high school teachers in making digital-based teaching materials to facilitate students in the learning process.Keywords: Learning, Teaching Materials, Teacher